PEMBAYARAN NON TUNAI: PERSEPSI CIVITAS AKADEMIKA FITK UIN MAULANA MALIK IBRAHIM MALANG - Julaihah, Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Non-cash payment has been promoted by Bank Indonesia since 2006 but, until now many people are still reluctant to use such facilities. This research uses descriptive quantitative research which aims to know the perception of the academic community of the Fakultas Tarbiyah dan Keguruan (FITK) UIN Maulana Malik Ibrahim Malang on usability, convenience, security and risks of non-cash transaction. The results showed that the respondents had a good perception on usability, convenience, security and risks of non-cash transactions. This research also finds that the student group is still using a single type of instrument ie. ATM transaction, while the lecturer-employees group is already using the ATM, SMS banking and Internet banking. Bank Indonesia is expected to educate the public continuously, so people have well financial literacy that would boost the success of non-cash transactions movement in Indonesia.Keywords: perception, payment, non cash